"Amongst the Most Desirable Reading": Advertising and the Fetters of the Newspaper Press in Britain, c. 1848–1914. (August 2019) - Rosenberg, Anat
Abstract : What is the difference between advertising and news? This essay examines the rise of this dilemma and its precarious resolution in the formative era of modern advertising and press commercialization in Britain, c. 1848–1914, with particular attention to legal powers mobilized in the process. The essay traces a dialectical process, which began with the midcentury campaign to repeal taxes on the press, one of which was the advertisement duty. The campaign framed advertising as a communication of essential information. Its success gave full reign to advertising in the newspaper press, but also triggered a readjustment: Newspaper owners soon faced a threat to their effective control of the medium; their proprietary power to differentiate advertising from their self-proclaimed business - news - was put to the test. Owners' responses established a hierarchic distinction between news and advertising, along an informational metric: advertising was framed as an inferior kind of information, more biased than news. The hierarchy became embedded as a common sense to the point that the process of historical creation has been forgotten; yet, it asserted a difference between news and ads which had little to hang on in theory and practice, giving rise to challenges which still resonate today.